Matrix Organization and Merit Factor Evaluation as a Method to Address the Challenge of Finding a Polymer Material for Roll Coated Polymer Solar Cells. Issue 10 (19th February 2015) - Bundgaard, Eva; Livi, Francesco; Hagemann, Ole; Carlé, Jon E.; Helgesen, Martin; Heckler, Ilona M.; Zawacka, Natalia K.; Angmo, Dechan; Larsen‐Olsen, Thue T.; dos Reis Benatto, Gisele A.; Roth, Bérenger; Madsen, Morten V.; et al.
<x xml:space="preserve">Abstract</x> The results presented demonstrate how the screening of 104 light‐absorbing low band gap polymers for suitability in roll coated polymer solar cells can be accomplished through rational synthesis according to a matrix where 8 donor and 13 acceptor units are organized in rows and columns. Synthesis of all the polymers corresponding to all combinations of donor and acceptor units is followed by characterization of all the materials with respect to molecular weight, electrochemical energy levels, band gaps, photochemical stability, carrier mobility, and photovoltaic parameters. The photovoltaic evaluation is carried out with specific reference to scalable manufacture, which includes large area (1 cm2), stable inverted device architecture, an indium‐tin‐oxide‐free fully printed flexible front electrode with ZnO/PEDOT:PSS (poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate), and a printed silver comb back electrode structure. The matrix organization enables fast identification of active layer materials according to a weighted merit factor that includes more than simply the power conversion efficiency and is used as a method to identify the lead candidates. Based on several characteristics included in the merit factor, it is found that 13 out of the 104 synthesized polymers outperformed poly(3‐hexylthiophene) under the chosen processing conditions and thus can be suitable for further development.